The use of field dependence of AC susceptibility for the interpretation of magnetic mineralogy and magnetic fabrics in the HSDP-2 basalts, Hawaii - Vahle, Carsten; Kontny, Agnes (Earth and planetary science letters, 2005)
We applied the field dependence parameter χHd (%)=[(k300A/m−k30A/m)/k300A/m]×100 given by de Wall for the subaerial and submarine basalts drilled by the 3109 m deep HSDP-2 borehole on Hawaii in order to verify the hypothesis that mainly composition controls the field dependence of AC susceptibility in titanomagnetite of natural occurrences. When we used this parameter, our data showed a significant scattering compared to data presented in earlier studies. In addition to composition, the effect of measurement temperature, grain size and anisotropy on the field dependent susceptibility were examined and found to be critical. The impact of grain size is weaker than the other effects. It cannot be totally excluded that the observed effects arise indirectly through an overlap of the other effects for the investigated basalts. The most important factor for the variation of field dependence is the degree of oxidation, causing a modification of the titanomagnetite composition or formation of titanomaghemite, and the mixing of Ti-rich with Ti-poor titanomagnetites, which strongly reduces the χHd parameter. Field dependence is not only related to titanomagnetite composition, especially for intermediate titanomagnetites with TCs between 100 and 300 °C. Temperature dependent susceptibility measurements at different field amplitudes for these intermediate types showed at constant geometry of the k(T) curve great differences in susceptibility, resulting in significant changes of the field dependence parameter over the temperature interval from −100 to 260 °C. Therefore variations of the ambient measurement temperatures are able to influence the field dependence. The second important effect is the degree of particle shape and alignment, which controls the field dependence in different orientations especially for the intermediate titanomagnetite, which is intensively intergrown with elongated hemoilmenite grains. As a consequence, samples with higher degrees of anisotropy exhibit differences of the field dependence parameter if measured parallel to kmax or kmin axis. Therefore, in addition to compositional effects and the temperature dependence, the magnetic fabric has to be considered for the interpretation of field dependent susceptibility measurements. The influence of intrinsic (Ti-content, magnetocrystalline anisotropy), and extrinsic (shape and alignment of grains) factors for the interpretation of the degree of anisotropy has to be kept in mind when interpreting AMS data in terms of strain rates experienced by moving lava during emplacement.
Gesehen am 24.09.2020